WORLD HEALTH ORGANIZATION: AN OVERVIEW - Amrita Mishra, Dr. Hiranmaya Nanda (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research paper discusses the overview of the World Health Organization which is one of the permanent bodies of the United Nations. This paper discusses the Objectives, Mechanisms and functionaries of the body. The paper begins with giving the introduction of the Organization by discussing its origin and principles on which it is based on. It also discusses the special features of the body. The Aim of the body, as has been laid down in Article 1 of the Constitution of the Organization and its Preamble has also been discussed. The paper further discusses the structure of the organization which is constituted of various bodies such as the Health Office, the executive board, the secretariat and the Regional Offices along with the national level offices. The paper concludes with talking about the importance of the functions performed by W.H.O and the need of the World Health Organization to be better equipped in order to combat the health related issues arising around the world in the 21st Century.